1174 THE ROLE OF HIP FRACTURE IN TRAJECTORIES OF DEPRESSIVE SYMPTOMS AMONG OLDER ADULTS: ANALYSIS FROM THE ENGLISH LONGITUDINAL STUDY. (16th January 2023) - Milton-Cole, R; Ayis, S; O'Connell, M D L; Smith, T; Sheehan, K
Abstract: Introduction: Older adults experience 'Late life depression'. Hip fractures may negatively influence trajectories of depressive symptoms in older adults. This study aimed to determine trajectories of depressive symptoms among older adults in England, overall and for those after hip fracture, and identify characteristics defining trajectory membership. Methods: Analysis of adults aged 60 years or more (n=7, 050), including a hip fracture subgroup (n = 384), from the English Longitudinal Study of Ageing. Latent class growth mixture modelling was completed. Depressive symptom prevalence was estimated at baseline. Chi-squared tests were completed to compare baseline characteristics across trajectories. Results: Three trajectory groups were identified overall and for those with hip fracture: no-, mild-, and moderate-severe- symptoms. The moderate-severe group comprised 13.7% and 7% of participants for overall and hip fracture populations respectively. Overall, the proportion of participants with depressive symptoms were 0.4%, 12.4% and 65.4% for no-, mild-, and moderate-severe- symptom groups, respectively. For the hip fracture subgroup, these proportions were 0.7%, 28.8%, and 85.2%. Depressive symptoms were stable over time, with a weak trend towards increasing severity for the moderate-severe group. Individuals with moderate-severe trajectories were older, more likely to be female, live alone and had worse health outcomes (p < 0.001). Conclusions: Older adults, and those after hip fracture, follow one of three trajectories of depressive symptoms which are broadly stable over time. The prevalence of depressive symptoms was lower for those with hip fracture however, when present, the symptoms were more severe than the overall population. Results suggest a role of factors including age, gender, and marital status in depressive symptoms trajectories.